INSTAGRAM AND THE MEMED SELF - Keye, Wade (AoIR Selected Papers of Internet Research, 2021)
The irreverent, bizarre and deeply political work of Instagram meme artists serves as a potent rejoinder to the claim that “the left can’t meme” In their commitment to a constantly moving mix of politics and absurdism, IG memers have something in common with the Alt-Right despite their completely opposed politics. Many of these well-followed accounts have developed a signature brand of humor and aesthetics while cultivating loyal fans. These “meme lords” are part of a recent wave in online culture I’m calling “weird Instagram.” Named for Facebook precursor, weird Instagram might best be differentiated by the much greater inclusion of self in meme production. In this paper I’ll discuss this phenomenon in its platform specificity, using the work of two prominent meme artists to exemplify the phenomenon.